Dell Inc. : managing reputation in the blogosphere (B) - Pulscher, Shawn; Provenzano, Nina; Rand, Clint; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
After deeming Dell's customer service unsatisfactory, Jeff Jarvis, a well-known Internet blogger, posted an extremely critical open letter to the company's CEO. Within a matter of days, Dell had a full-blown crisis on its hands and was forced to reconsider how to deal with emerging technological platforms used by customers to communicate information and opinions.
Originally published in Pulscher, S., Provenzano, N., Rand, C., & ORourke, J. S. (2009). Dell Inc.: Managing reputation in the blogosphere (B). 09-02 (B). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Dell Inc; Consumer satisfaction; Blogs; Social media; Brand loyalty; Computer industry